Connaught Tunnel, UK: condition and repairs. Issue 2 (February 2019) - Wilde, David
Abstract : The aims of this paper are to record how the Connaught Tunnel was surveyed, assessed and repaired by Crossrail for use for the new Elizabeth line in London, UK. The challenges and changes involved with implementing the repairs required to bring an example of Victorian engineering back into use again were based on Network Rail guidance and other current practice. The repairs will reduce future maintenance requirements, which will benefit railway operations in the future. Groundwater leakage remains within the tunnel as the cost of rectifying the leaks, if successful, would have been prohibitive. Prior to the Crossrail Act of 2008, consideration was given to the whole-life costing of reusing the tunnel as opposed to boring new tunnels, and the cost of new tunnels was considered to be higher than the costs of repairs, maintenance and ongoing drainage requirements to reuse the existing tunnel.